Peripapillary and Subfoveal Choroidal Thickness in Retinal Vein Occlusions - Moleiro AF; Godinho G; Madeira C; Faria Pereira A; Brandão E; Falcão-Reis F; Beato JN; Penas S (Clinical Ophthalmology, 2022)
Ana Filipa Moleiro,1,2 Gonçalo Godinho,3 Carolina Madeira,4 Ana Faria Pereira,1 Elisete Brandão,1 Fernando Falcão-Reis,1,2 João Nuno Beato,1,2 Susana Penas1,2 1Department of Ophthalmology, Centro Hospitalar e Universitário de São João, Porto, Portugal; 2Department of Surgery and Physiology, Faculdade de Medicina da Universidade do Porto, Porto, Portugal; 3Department of Ophthalmology, Centro Hospitalar de Leiria, Leiria, Portugal; 4Department of Ophthalmology, Centro Hospitalar Gaia-Espinho, Gaia, PortugalCorrespondence: Ana Filipa Moleiro, Department of Ophthalmology, Centro Hospitalar e Universitário de São João, Alameda Hernani Monteiro, Porto, 4200-426, Portugal, Tel +351 915689259, Email anafomoleiro@gmail.comPurpose: This work aimed to longitudinally assess the peripapillary (PPCT) and subfoveal (SFCT) choroidal thickness (CT), in patients diagnosed with central (CRVO) or branch retinal vein occlusions (BRVO), correlating SFCT with central macular thickness (CMT) and PPCT with peripapillary retinal nerve fiber layer thickness (pRNFL).Patients and Methods: This was a retrospective longitudinal study of 71 eyes from 71 patients with treatment-naïve retinal vein occlusion (24 CRVO and 40 BRVO). Spectral-domain optical coherence tomography (SD-OCT, Spectralis HRA-OCT, Heidelberg) was used to measure PPCT, SFCT, pRNFL and CMT of the affected and fellow eyes at baseline (acute phase) and at 3 and 9 months post anti-VEGF treatment. IBM SPSS Statistics version 27.0 (IBM Corp., Armonk, NY, USA) was used for statistical analysis. A p-value ≤ 0.05 was considered statistically significant.Results: Affected eyes presented a thicker baseline PPCT and SFCT compared to their fellow eyes both in CRVO and BRVO (p < 0.05). Both groups presented a significant decrease of PPCT in the affected eyes at 3 months compared to baseline (p < 0.05). At 9 months, compared to 3 months, PPCT remained stable (p > 0.05). Similarly, affected eyes’ SFCT significantly decreased at 3 months (p < 0.05) in both groups. At 9 months, compared to 3 months, SFCT decreased in the CRVO patients (p = 0.047) but remained stable in the BRVO patients (p = 0.850). No correIations between SFCT and CMT were seen at any timepoint in both groups (p > 0.05). PPCT correlates with pRNFL in CRVO at 3 months, although no other correlations were found during the follow-up. In BRVO, PPCT did not show any significant correlation with pRNFL.Conclusion: Both in CRVO and BRVO eyes, PPCT and SFCT at diagnosis are significantly thicker compared to the fellow eye, suggesting a possible increase in CT immediately after the occlusion, which is followed by a decrease at an early follow-up stage.Keywords: biomarkers, vascular retinal diseases, retinal vein occlusions, choroidal thickness, optical coherence tomography